2016
DOI: 10.1158/1078-0432.ccr-15-1488
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Expression of Genes Representing Key Biologic Processes after Neoadjuvant Chemotherapy in Breast Cancer, and Prognostic Implications in Residual Disease

Abstract: Purpose: The primary aim was to derive evidence for or against the clinical importance of several biologic processes in patients treated with neoadjuvant chemotherapy (NAC) by assessing expression of selected genes with prior implications in prognosis or treatment resistance. The secondary aim was to determine the prognostic impact in residual disease of the genes' expression. Experimental Design: Expression levels of 24 genes were quantified by NanoString nCounter on formalin-fixed paraffin-emb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 53 publications
4
37
0
Order By: Relevance
“…For example, DCN (decorin) regulates PGR by competing for miR-19b-1-5p and promotes the basal-like subtype (Pearson correlation coefficient =0.54). This supports previous findings that DCN is down-regulated and influences the breast cancer cell motility and invasion, and acts as one of the six-gene signature that adds prognostic value independent of the expression of ER, PR, and HER2 [51, 52]. Therefore, subtype specific expression of 50-gene in PAM50 model can be regulated by other ceRNAs that may influence breast cancer subtype specificity.…”
Section: Discussionsupporting
confidence: 90%
“…For example, DCN (decorin) regulates PGR by competing for miR-19b-1-5p and promotes the basal-like subtype (Pearson correlation coefficient =0.54). This supports previous findings that DCN is down-regulated and influences the breast cancer cell motility and invasion, and acts as one of the six-gene signature that adds prognostic value independent of the expression of ER, PR, and HER2 [51, 52]. Therefore, subtype specific expression of 50-gene in PAM50 model can be regulated by other ceRNAs that may influence breast cancer subtype specificity.…”
Section: Discussionsupporting
confidence: 90%
“…However, the consistently significant associations between LC3B and prognosis were restricted to the luminal B and triple‐negative subtypes. Klintman et al identified 14 genes which were significantly associated with time to recurrence in residual disease after NAC. Of these genes, the 6‐gene signature consisting of genes representing proliferation, metabolism, stromal response, immunologic response and estrogen signaling had additional prognostic significance independent of ER and HER2 status.…”
Section: Discussionmentioning
confidence: 99%
“…Par-4 mRNA was upregulated following chemotherapy and Par-4 had a significant impact on prognostic, dependent of the ER status. Indeed, Par-4 level was predictive of a good outcome in ER- patients and the opposite was observed in ER+ patients indicating an important role for hormones and Par-4 [312]. As introduced, few studies demonstrated that estrogen can downregulate Par-4 [177, 178].…”
Section: Targeted Therapies To Overcome Chemoresistancementioning
confidence: 99%